1985
DOI: 10.1002/pssb.2221320215
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of Amorphous Fe90.6Zr9.4

Abstract: The temperature dependence of the spontaneous magnetization, M,, and the magnetization curve of melt-spun amorphous Fego.6Zrg.a alloys are investigated by means of a SQUID magnetometer in the temperature range 4.2 K < T < 150 K, and for magnetic fields 1 mT < poH < 4 T. At low magnetic fields, poH < 80 mT, M , is found to obey a F l a w whereas for poH > 0.27 T Bloch's TW-law is obtained. No evidence for a spin-glass transition a t low temperatures can be detected. The high-field susceptibility points to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

1988
1988
1998
1998

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 16 publications
0
9
1
1
Order By: Relevance
“…The last term in equation ( 23) is normally too small to merit consideration because the coefficient B usually has a value close to zero (note that depending upon the structure of the DOS curve and hence on the relative magnitude of its derivatives, B can be either positive, negative or zero) but it can be significant for systems in which S has an extremely large value, i.e., for very weak itinerant ferromagnets in which I N(E F ) → 1 and hence S → ∞. From the coefficient of the T 2 -term in equation (23), it is evident that LSF (Stoner SP excitations) dominantly contribute to M(T , 0) if T 0 T S C (T S C T 0 ). However, if T 0 ≈ T S C , the contributions due to LSF and SP excitations are comparable in magnitude.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…The last term in equation ( 23) is normally too small to merit consideration because the coefficient B usually has a value close to zero (note that depending upon the structure of the DOS curve and hence on the relative magnitude of its derivatives, B can be either positive, negative or zero) but it can be significant for systems in which S has an extremely large value, i.e., for very weak itinerant ferromagnets in which I N(E F ) → 1 and hence S → ∞. From the coefficient of the T 2 -term in equation (23), it is evident that LSF (Stoner SP excitations) dominantly contribute to M(T , 0) if T 0 T S C (T S C T 0 ). However, if T 0 ≈ T S C , the contributions due to LSF and SP excitations are comparable in magnitude.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, if T 0 ≈ T S C , the contributions due to LSF and SP excitations are comparable in magnitude. Recognizing that equation (23) can be put into the form [M(T , 0)/M(0, 0)] 2 = 1 − 2AT 2 + A 2 T 4 , equation (23) can be generalized to…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of low-lying magnetic excitations in a-Fe 90+y Zr 10−y (0 y 3) alloys has lately given rise to much controversy. While Krishnan et al [4] found that the 'infield' magnetization varies with temperature as M(H, T ) ∝ T 3/2 for T > T * (H ) in external magnetic fields up to 140 kOe for a-Fe 90 Zr 10 and that the spin-wave (SW) stiffness coefficient D increases with increasing H , attaining a maximum value of 39.1 meV Å2 , Beck and Kronmüller [5] observed that the thermal demagnetization in the temperature range 4.2 K T 0.5T C is solely due to Stoner single-particle (SP) excitations (SW excitations) for H < 2.7 kOe (H > 2.7 kOe) and D decreases from 50 to 35 meV Å2 as H is increased from 2.7 to 40 kOe. The observation based on inelastic neutron scattering (INS) experiments on a-Fe 91 Zr 9 , that no propagating features [6] were evident at any temperature below T C for the wavevector transfer range 0.05 Å−1 q 0.12 Å−1 , complicated the issue further.…”
Section: Introductionmentioning
confidence: 99%
“…(13.14). υαλώδεις δομές σπιν (ΥΔΣ, x=7), στις οποίες λαμβάνει χώρα μόνο μια μετάβαση από την παραμαγνητική στην υαλώδη κατάσταση σπιν σε θερμοκρασία T g [Hiroyoshi and Fukamichi 1981, Kaul 1983, Read et al 1984, Beck and Kronmueller 1985. Η θερμοκρασία T c μεταβάλλεται έντονα με τη συγκέντρωση και Για το σύστημα Fe9oZr I0 οι θερμοκρασίες μετάβασης στη σιδηρομαγνητική κατάσταση και στην κατάσταση υαλώδους δομής σπιν έχουν βρεθεί T c =210 Κ και Tf=80 Κ, αντίστοιχα [Hiroyoshi and Fukamichi 1981, 1983, Obi et al 1982, Krishman et al 1984 .…”
Section: περιγραφή πειραματικών διεργασιώνunclassified